Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(-5\left(-x+7\right)-3\left(-x-5\right)=-4\left(12-x\right)+48\)
\(\Leftrightarrow5x-35+3x+15=-48+4x+48\)
\(\Leftrightarrow4x=20\)
\(\Rightarrow x=5\)
b) \(-2\left(15-3x\right)-4\left(-7x+8\right)=-5-9\left(-2x+1\right)\)
\(\Leftrightarrow-30+6x+28x-32=-5+18x-9\)
\(\Leftrightarrow16x=48\)
\(\Rightarrow x=3\)
c) \(7\left(-x-7\right)-5\left(-x-3\right)=12\left(3-x\right)\)
\(\Leftrightarrow-7x-49+5x+15=36-12x\)
\(\Leftrightarrow10x=70\)
\(\Rightarrow x=7\)
d) \(5\left(-3x-7\right)-4\left(-2x-11\right)=7\left(4x+10\right)+9\)
\(\Leftrightarrow-15x-35+8x+44=28x+70+9\)
\(\Leftrightarrow35x=-70\)
\(\Rightarrow x=-2\)
e) \(-2\left(x+3\right)-15=3\left(4+2x\right)+7\)
\(\Leftrightarrow-2x-6-15=12+6x+7\)
\(\Leftrightarrow8x=-40\)
\(\Rightarrow x=-5\)
B2:tìm x biết
1)x+18=6-2x
<=> 3x=-12
<=> x= -4
2)17-x=7-6x
<=>5x=-10
<=>x=-2
3)x+15=20-4x
<=>5x=5
<=>x=1
4)7x-4=20+3x
<=> 4x=24
<=>x=6
5)-12+x=5x-20
<=>4x=8
<=>x=2
6)4x-18=x+27
<=>3x=45
<=>x=9
7) 2.(x-5)-3.(x+7)=14
<=>2x-10-3x-21=14
<=>-x=14+10+21=45
<=>x=-45
8)5.(x-6)-2.(x+3)=12
<=>5x-30-2x-6=12
<=>3x=48
<=>x=12
9)-7.(5-x)-2.(x-10)=15
<=>-35+7x-2x+20=15
<=>5x=30
<=>x=6
10)3. ( x - 4 ) - ( 8 - x )=12
<=>3x-12-8+x=12
<=>4x=32
<=>x=8
11)4.(x-5)-(x+7)=-19
<=>4x-20-x-7=-19
<=>3x=8
<=>x=8/3
12)7.(x-3)-5.(3-x)=11x-5
<=>7x-21-15+5x=11x-5
<=>x=31
b1:bỏ ngoặc rồi tinh hợp lí
1) -( -66)+34+(-73)-27+99=66+34-73-27+99 =100-100+99=99
2)54-(45-30+54)-30+5=54-45+30-54-30+5=-45+5=-40
3)42-56+33-(33-56+42)=42-56+33-33+56-42=0
4)50-(47+50-18)+(47-18)=50-47-50+18+47-18=0
5) |25-24-10|-(28-30+4)=9-28+30-4=39-32=7
6)-(-73)+(44-94+27)+94=73+44-94+27+94=100+44=144
7) (-33+180-75)-(180+25)=-33+180-75-180-25=-100-33=-133
8)120-(-92+120-18)-92=120+92-120+18=108
1) 2(x - 5) - 3(x + 7) = 14
2x - 10 - 3x - 21 = 14
2x - 3x = 14 + 21 + 10
- x = 45
x = -45
2) 5(x - 6) - 2(x + 3) = 12
5x - 30 - 2x - 6 = 12
3x = 12+ 30 + 6
3x = 48
x = 16
3) -7(5 - x) - 2(x - 10) = 15
-35 + 7x - 2x + 20 = 15
5x = 15 - 20 + 35
5x = 30
x = 6
4) 3(x - 4) - (8 - x) = 12
3x - 12 - 8 + x =12
4x = 12 + 8 + 12
4x = 32
x = 8
5) 4(x - 5) - 3(x + 7) = -19
4x - 20 - 3x - 21 = -19
x = -19 + 21 + 20
x = 22
6) 7(x - 3) - 5(3 - x) = 11x - 5
7x - 21 - 15 + 5x = 11x - 5
7x + 5x - 11x = -5 + 21 + 15
x = 31
7) 4(2 - x) + 3(x - 5) = 14
8 - 4x + 3x - 15 = 14
- x = 14 + 15 - 8
- x = 21
x = -21
1
a, 15 - ( 4 - x ) = 6
<=> 4 - x = 6 - 15
<=> 4 - x = -9
<=> x = -9 + 4
<=> x = -5
Mấy câu kia dễ tự làm :>
\(15-\left(4-x\right)=6\)
\(\Rightarrow4-x=9\)
\(\Rightarrow x=-5\)
1) 2(x + 5) + 3(x + 7) = 41
2x + 10 + 3x + 21 = 41
5x + 31 = 41
5x = 10
x = 2
6) 7(x - 1) + 5(3 - x) = 11x - 10
7x - 7 + 15 - 5x = 11x - 10
2x + 8 = 11x - 10
-9x = -18
x = 2
2) 5(x + 6) + 2(x - 3) = 38
5x + 30 + 2x - 6 = 38
7x + 24 = 38
7x = 14
x = 2
7) 4(2 + x) + 3(x - 2) = 12
8 + 4x + 3x - 6 = 12
7x + 2 = 12
7x = 10
x = 10/7
3) 7(5 + x) + 2(x - 10) = 15
35 + 7x + 2x - 20 = 15
9x + 15 = 15
9x = 0
x = 0
8) 5(2 + x) + 4(3 - x) = 10x - 15
10 + 5x + 12 - 4x = 10x - 15
x + 22 = 10x - 15
9x = 37
x = 37/9
4) 3(x + 4) + (8 - 2x) = 22
3x + 12 + 8 - 2x = 22
x + 20 = 22
x = 2
9) 7(x - 2) + 5(3 - x) = 11x - 6
7x - 14 + 15 - 5x = 11x - 6
2x + 1 = 11x - 6
-9x = -7
x = 7/9
5) 4(x + 5) + 3(7 - x) = 49
4x + 20 + 21 - 3x = 49
x + 41 = 49
x = 8
10) 5(3 - x) + 5(x + 4) = 6 + 4x
15 - 5x + 5x + 20 = 6 + 4x
35 = 6 + 4x
4x = 29
x = 29/4